FGM stainless steel-Ti(C, N) cermets through colloidal processing. (March 2015) - Escribano, J.A.; García, J.L.; Alvaredo, P.; Ferrari, B.; Gordo, E.; Sanchez-Herencia, A.J.
Abstract: In this work, the colloidal approach was used to promote a gradation in the composition of a cermet, based on the mixture of stainless steel and Ti(C, N) during powder consolidation into a bulk part. The colloidal processing of non-oxides in aqueous media requires an elevated control over the evolution of the surface chemistry of the powders, in order to obtain stable and high concentrated slurries of the mixture of metal/non-oxide ceramic. The advantage of those methods lies on the fabrication of complex micro-architectures where the second phases are intimately and homogeneously dispersed in the microstructure of the composite. Moreover, those techniques allow the processing of fine particles with low compressibility and flowability which difficult conventional powder metallurgical processing. The results shown in this work evidence the feasibility of obtaining continuous functionally graded materials (FGM) through slip casting in porous molds, as well as the relevance of the rheological properties of the composite slurries on the final characteristics of the material. Highlights: Functionally graded 430 L/Ti(C, N) materials were prepared by colloidal techniques. Rheology of the suspensions directly influenced on the gradient of the materials. Homogeneity of the dispersions allowed processing cermets with 70% vol Ti(C, N). Cermets obtained/shaped by slip casting present an increase in hardness compared to those obtained by powder metallurgy techniques. Cermets shaped by slip casting present higher hardness than those processed by PM.